Analisis Determinan Pembangunan Manusia Berbasis Gender Dan Desentralisasi Fiskal Pada Inklusifitas Pertumbuhan Ekonomi Di Provinsi Nusa Tenggara Barat - Hevi Novita Ramandani (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
This research aims to examine the influence of gender and fiscal decentralization on inclusive economic growth in West Nusa Tenggara Province. This research uses a panel data regression analysis method using the Fixed Effect Model approach to determine the influence of the dependent variable on the independent variable. As a result, the gender-based development index variable, namely the ratio of average years of schooling, has a positive and significant value; the ratio of life expectancy and the open unemployment rate ratio has a negative value and is not substantial; the variable of the degree of fiscal decentralization, namely the ratio of the degree of fiscal decentralization and the capital expenditure ratio, has a value positive and significant towards inclusive economic growth in West Nusa Tenggara Province.